Agroforests, Swiddening and Livelihoods between Restored Peat Domes and River: Effects of the 2015 Fire Ban in Central Kalimantan (Indonesia) - Silvianingsih, Y.A.; Hairiah, K.; Suprayogo, D.; Noordwijk, M. van (Commonwealth Forestry Association, 2020)
If 150 years of continued use counts as a sustainability indicator, the river-bank agroforests in the peat landscapes of Central Kalimantan suggest solutions for current challenges. The 2015 fire season in Indonesian peatlands triggered a fire ban and peatland restoration response, prioritizing canal blocking and rewetting. However, sustainable livelihood options remain elusive. We report local ecological knowledge of soils and vegetation applied in land use choices in swiddens and agroforests in five Dayak Ngaju villages in Jabiren Raya and Kahayan Hilir subdistrict (Pulang Pisau, C. Kalimantan, Indonesia) on the banks of the Kahayan river and discuss impacts of fire-ban policies. Plots accessible from the river with no or shallow peat were traditionally preferred for swiddening, with various indicator plants and soil characteristics underpinning the choices. Without swiddening farmers depend on off-farm jobs and agroforests for income. More policy attention for non-peat riparian-zone agroforestry as part of peat landscape livelihood systems is warranted.